Special Local Need Pesticide Registrations--24(c) - Frederick M. Fishel (EDIS)
This document describes a unique type of pesticide registration – Special Local Need, also known as a 24(c) registration, and examples of situations where it is warranted. This document is PI-95, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date January 2006.